Minat Peserta Didik terhadap Senam Kebugaran Jasmani Indonesia Bersatu (SKJ 2018) - Made Armade; Masdi Janiarli; Lolia Manurizal (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aims to determine the interest of students in participating in United Indonesia Gymnastics (SKJ 2018) at SMA N 1 Rambah, Rokan Hulu Regency. This type of descriptive qualitative research. The population is 874 students and the sample is 30 students using purposive sampling technique. The method used in this research is a questionnaire method. The stages of the method that will be passed in this study are starting from observation, interviews and then continuing with the distribution of questionnaires to each student. The results showed that the achievement level of student interest was in a good classification, with the respondent's answer achievement level reaching 65%. The conclusion in this study is that students' interest in participating in United Indonesia Gymnastics (SKJ 2018) at SMA Negeri 1 Rambah is good. Keywords: Interests, Students, Physical Fitness Gymnastics